The Prevalence of Tooth Wear in the Adult Population - TONG MINH SON (Journal of Global Pharma Technology, 2018)
Objective: To evaluate the prevalence of tooth wear in the Vietnam adult population in different age groups, for both genders, in different socioeconomic classes, and for different types of teeth. Methods: A total of 800 patients of either gender, ages 18 – 60 years were placed into group A (acid-directly exposed) and group B (acid-indirectly exposed). We recorded the prevalence and severity of tooth wear (TW). TW was measured clinically by Smith and Knight Index. This study included a dentine hypersensitivy (DH) testing device (Yeaple Probe) in addition to the current visual analog scale (VAS) methods of dentine hypersensitivy testing. Results: A total of 400 patients of group A, out of which 366 patients were diagnosed with tooth wear giving an overall prevalence of 91.5 %. In group B a total 400 patients were investigated out of which 344 (86.0 %) patients showed signs of tooth wear. From a total of 32247 teeth (400 faces) examined 4677 (14.5 %) showed dentine hypersensitive on tooth surface in group A. In group B total 32460 teeth (400 faces) were investigated out of which 1720 (5.3 %) teeth showed signs of dentine hypersensitive. Conclusion: Tooth wear is the prevalent condition in this population. Further investigations and continuous follow-up of cases may allow the mapping of the relationship of biological factors with the occurrence of tooth wear.Keywords: Tooth wear, Dentine hypersensitive, Visual analog scale.